+0  
 
0
192
2
avatar+2509 

Help.

NotSoSmart  Dec 8, 2017
 #1
avatar+87293 
+1

10.  x^3  - 5x^2 + 3x + 9  = 0

 

Rewrite as

 

x^3 - 5x^2 - 6x + 9x + 9  = 0

 

x(x^2 - 5x - 6) + 9(x + 1)  = 0

 

x (x - 6)(x + 1)  +  9 (x + 1)  = 0

 

(x + 1) [ x (x - 6) + 9 ]  = 0

 

(x + 1)  [ x^2 - 6x + 9 ]   = 0

 

(x + 1) (x - 3)(x - 3)  = 0

 

Three real roots.....two equal in value

 

 

cool cool cool

CPhill  Dec 8, 2017
 #2
avatar+87293 
+1

11.  ( s + v)5

 

Second term is    C(5,1)s4v  =  5s4v

 

 

 

cool cool cool

CPhill  Dec 8, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.